Pengaruh Stres Kerja, Motivasi Kerja, dan Disiplin Kerja Terhadap Produktivitas Kerja Karyawan Studi Kasus PT Mitsui Kinzoku Catalysts Jakarta - Zidan Maulana Ibrahim; Rahmat Hidayat; Saur Panjaitan; Ahmad Gunawan (Jurnal Ilmiah Wahana Pendidikan, 2023)
This research was conducted to identify significant differences between work stress, work motivation, and work discipline on the work productivity of employees that occur, using a case study of PT Mitsui Kinzoku Catalysts Jakarta. This type of research is quantitative, namely data used to examine a population and samples, namely ordinal data obtained from questionnaire results. The essence of this type of quantitative research is to advance and utilize mathematical means. In this study, the population used was 114 employees of the production department at PT Mitsui Kinzoku Catalysts Jakarta. The methods used by researchers to collect various data, information, and other supporting facts for research purposes are literature studies, observations, questionnaires, and documentation. The analytical techniques used to process data in this study include using instrument tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and intervening tests. Based on the overall results of tests that have been carried out with IBM SPSS 25 software, it was found that work stress, work motivation and work discipline together (simultaneously) have a significant influence on employee work productivity at PT. Mitsui Kinzoku Catalysts Jakarta. This indicates the scale of productivity in the work of PT. Mitsui Kinzoku Catalysts Jakarta can be measured based on previous variables that have a major influence on employee work productivity.